Synthesized and characterization of sodium cobalt oxide as sodium-ion cathode batteries using sol-gel method [Sintesis dan pencirian sodium kobalt oksida sebagai katod bateri ion-sodium menggunakan kaedah sol-gel] - Mohd Jan, Sarah Laila; Mohd Azhar, Nur Athirah; Jani, Musfiroh (Scopus, 2018)
Sodium’s chemical properties are like lithium and as batteries it has potential to be environmentally friendly, easier to recycle but five times much cheaper than lithium-ion batteries. Sodium cobalt oxide (NaCoO2 ) cathode material in a sodium-ion battery was synthesized by a polyvinyl alcohol (PVA) assisted sol-gel method and its physical characterization was being analysed by using thermogravimetric analysis (TGA), attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectroscopy, field emission scanning electron microscope (FESEM) and X-ray diffractometer (XRD). PVA was chosen as gelating agent as well as carbon source for the synthesized material in this study. The cathode material is observed to have smooth morphology and the particle sizes reach to sub-micrometre level which benefit for the high rate performance, although the shape of particles was irregular.